Kill two birds with one stone: Engineered exosome-mediated delivery of cholesterol modified YY1-siRNA enhances chemoradiotherapy sensitivity of glioblastoma - Liu, Xiao; Cao, Zhengcong; Liu, Nannan; Gao, Guangxun; Du, Mingrui; Wang, Yingwen; Cheng, Boyang; Zhu, Maorong; Jia, Bo; Pan, Luxiang; Zhang, Wangqian; Jiang, Yuran; et al. (Frontiers in Pharmacology, 2022)
Glioblastoma (GBM) is the most malignant tumor of the central nervous system in adults. Radiotherapy and temozolomide (TMZ) play an extremely important role in the treatment of GBM. However, major impediments to effective treatment are postoperative tumor recurrence and acquired resistance to chemoradiotherapy. Our previous studies confirm that Yin Yang 1 (YY1) is highly expressed in GBM, whereby it is associated with cell dedifferentiation, survival, and therapeutic resistance. Targeted delivery of small interfering RNA (siRNA) without blood-brain barrier (BBB) restriction for eradication of GBM represents a promising approach for therapeutic interventions. In this study, we utilize the engineering technology to generate T7 peptide-decorated exosome (T7-exo). T7-exo shows excellent packaging and protection of cholesterol-modified Cy3-siYY1 while quickly releasing payloads in a cytoplasmic reductive environment. The engineered exosomes T7-siYY1-exo could deliver more effciently to GBM cells both in vitro and in vivo. Notably, in vitro experiments demonstrate that T7-siYY1-exo can enhance chemoradiotherapy sensitivity and reverse therapeutic resistance. Moreover, T7-siYY1-exo and TMZ/IR exert synergistic anti-GBM effect and significantly improves the survival time of GBM bearing mice. Our findings indicate that T7-siYY1-exo may be a potential approach to reverse the chemoradiotherapy resistance in GBM.